1982
DOI: 10.1039/p19820000767
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of forskolin, a biologically active diterpenoid from Coleus forskohlii

Abstract: Forskolin (1 ) (7P-acetoxy-8,13-epoxy-l a,6fJ,9a-trihydroxylabd-l4-en-11 -one), the major diterpenoid of Coleus forskohlii, has potent positive inotropic, antihypertensive, and adenylate cyclase stimulant properties. The reactivity of its various functional groups (1 a-OH, 6P-OH, the derived 7P-OH, 9a-OH, 11 -oxo, and 14,15-double bond) has been studied through acylation, alkylation, dehydration, oxidation, and reduction reactions. Pharmaceuticals Limited, Bombay -400 080, India

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In the most recent and arguably most impressive example, a series of polyglycosides were oxidized by Waymouth’s catalyst in 30–60% yields at the terminal sugar 23 . Prior to this study, the polyketide antibiotic mupirocin methyl ester was oxidized by the combination of TEMPO ((2,2,6,6-tetramethylpiperidin-1-yl)oxyl), NaOCl and KBr to give only a 31% yield of a monooxidation product 24 , and the labdane diterpene forskolin was oxidized by stoichiometric CrO 3 /pyridine in an 80% yield 25 , whereas another labdane diterpene, andrographolide, was oxidized to the 3-ketone in only a 5% yield under the optimized conditions 26 . These studies illustrate that the conditions developed for the reaction of one structure do not translate into the oxidation of another structure of the same or different class, and some molecules have resisted selective oxidation under all known conditions 2729 .…”
Section: Resultsmentioning
confidence: 99%
“…In the most recent and arguably most impressive example, a series of polyglycosides were oxidized by Waymouth’s catalyst in 30–60% yields at the terminal sugar 23 . Prior to this study, the polyketide antibiotic mupirocin methyl ester was oxidized by the combination of TEMPO ((2,2,6,6-tetramethylpiperidin-1-yl)oxyl), NaOCl and KBr to give only a 31% yield of a monooxidation product 24 , and the labdane diterpene forskolin was oxidized by stoichiometric CrO 3 /pyridine in an 80% yield 25 , whereas another labdane diterpene, andrographolide, was oxidized to the 3-ketone in only a 5% yield under the optimized conditions 26 . These studies illustrate that the conditions developed for the reaction of one structure do not translate into the oxidation of another structure of the same or different class, and some molecules have resisted selective oxidation under all known conditions 2729 .…”
Section: Resultsmentioning
confidence: 99%
“…6 This is the first report on 1-3 as naturally occurring substances, although they are already known as semisynthetic derivatives. 6-O-Acetylforskolin (1) and 1,6-di-Oacetylforskolin (2) have previously been obtained by acetylation of forskolin (4), 7 whereas 3 (1,6-di-O-acetyl-9-deoxyforskolin) has been reported as an intermediate in a semisynthesis of 4 starting from 9-deoxyforskolin (5). 8,9 Structures 1-3 were established by NMR spectroscopic studies and, since only partial 1 H NMR data for 1 and 2 had been reported, 7 we decided to perform the complete assignment of the 1 H and 13 C NMR spectra of these substances in order to provide several sets of data that might serve as models for future assignments of other structurally related compounds.…”
Section: Introductionmentioning
confidence: 99%
“…(1H, br s, 1b-H), 1.99 (1H, m, 2a-H), 2.03 (1H, m, 2b-H), 1.00 (1H, m, 3a-H), 1.06 (1H, m, 3b-H Oxidation of 4 and 5 The oxidation of 4 and 5 was performed following the procedure described by Bhat et al 19) To a stirred suspension of Collins reagents (8.0 mg) in methylene chloride (3 ml) was added a solution of 4 (4.0 mg) and 5 (2.7 mg) in methylene chloride (2 ml), respectively. The mixture was stirred at room temperature for 2.5 h and filtered.…”
Section: Methodsmentioning
confidence: 99%
“…Forskoditerpenoside B (2) 19,20) The sugar moiety was identified as b-Dglucopyranoside by acid hydrolysis and the coupling constant (Jϭ7.7 Hz) of H-1Ј. As listed in Table 2, the downfield shift of ϩ10.9 (d 85.5) observed for C-1, compared with that in 6-acetylforskolin, and correlation in the HMBC spectrum between C-1 and H-1Ј, indicated that the glucose was attached to C-1.…”
mentioning
confidence: 99%